2013
DOI: 10.1177/0022219413505773
|View full text |Cite
|
Sign up to set email alerts
|

How University Students With Reading Difficulties Are Supported in Achieving Their Goals

Abstract: We examine (a) what social ties university students with a history of reading difficulty (RD) report assisting them to achieve their goals, (b) outlets available for developing social ties, (c) resources mobilized within these relationships, and (d) the impact of social ties' status on academic achievement. Participants were 107 university students with RD who were currently completing or had recently completed a university degree. Results showed that university students with RD named friends, parents, and sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 53 publications
1
15
0
2
Order By: Relevance
“…Department of Education, 2014). In a recent study, 79% of university students with reading disabilities reported parents to be critical in helping them reach their goals during their undergraduate careers (Stack-Cutler, Parrila, Jokisaari, & Nurmi, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Department of Education, 2014). In a recent study, 79% of university students with reading disabilities reported parents to be critical in helping them reach their goals during their undergraduate careers (Stack-Cutler, Parrila, Jokisaari, & Nurmi, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…However, other research has addressed these issues (e.g., Gerber, Ginsberg, & Reift, 1992; Stack-Cutler, Parrila, Jokisaari, & Nurmi, 2013), which merit further research. Future research should also focus on other handicapping conditions affecting reading and writing in adolescents and young adults such as attention deficit disorder (Zuckerman, Lee, Odom, Solomon & Sills, 2013), mild head injuries (Beers, Goldstein, & Katz, 1994), and concussions (Alosco, Fedor, & Gunstad, 2014; Collins et al, 1999; Griffin, 2015; Covassin, Elbin, McAllister, & Whalen, 2014; Hunt, McCamey, & Beisner, 2010; Solomon & Haase, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In Stack-Cutler et al (2015), practice centred around strategies for addressing reading difficulties-information related to schools, problem solving, and emotional support. In Griffiths et al (2012), the individuals shared information with their doctors and built community.…”
Section: Towards a Reconceptualization Of Social Media Use By Indivmentioning
confidence: 99%